The randomised Oslo study of renal denervation vs. Antihypertensive drug adjustments: efficacy and safety through 7 years of follow-up - Ola Undrum Bergland; Camilla Lund Søraas; Anne Cecilie K. Larstorp; Lene V. Halvorsen; Ulla Hjørnholm; Pavel Hoffman; Aud Høieggen; Fadl Elmula M. Fadl Elmula (Blood Pressure, 2021)
Purpose The blood pressure (BP) lowering effect of renal sympathetic denervation (RDN) in treatment-resistant hypertension shows variation amongst the existing randomised studies. The long-term efficacy and safety of RDN require further investigation. For the first time, we report BP changes and safety up to 7 years after RDN, compared to drug adjustment in the randomised Oslo RDN study. Materials and methods Patients with treatment-resistant hypertension, defined as daytime systolic ambulatory BP ≥135 mmHg after witnessed intake of ≥3 antihypertensive drugs including a diuretic, were randomised to either RDN (n = 9) or drug adjustment (n = 10). The initial primary endpoint was the change in office BP after 6 months. The RDN group had their drugs adjusted after 1 year using the same principles as the Drug Adjustment group. Both groups returned for long-term follow-up after 3 and 7 years. Results The decrease in office BP and ambulatory BP (ABPM) after 6 months did not persist, but gradually increased in both groups. From 6 months to 7 years follow-up, mean daytime systolic ABPM increased from 142 ± 10 to 145 ± 15 mmHg in the RDN group, and from 133 ± 11 to 137 ± 13 mmHg in the Drug Adjustment group, with the difference between them decreasing. In a mixed factor model, a significantly different variance was found between the groups in daytime systolic ABPM (p = .04) and diastolic ABPM (p = .01) as well as office diastolic BP (p<.01), but not in office systolic BP (p = .18). At long-term follow-up we unveiled no anatomical- or functional renal impairment in either group. Conclusions BP changes up to 7 years show a tendency towards a smaller difference in BPs between the RDN and drug adjustment patients. Our data support RDN as a safe procedure, but it remains non-superior to intensive drug adjustment 7 years after the intervention.